Collaborative Τeaching as a Social form of Organizing Teaching in Primary Education: Views and Attitudes of Greek Teachers - Evangelou, Filippos (International Journal of Learning and Development, 2024)
The purpose of this study is to investigate the views and attitudes of active Greek teachers in Primary Education on the implementation of Collaborative Teaching (CT) as a social form of teaching organization regarding the way of cooperation and organization of relationships between students during the teaching and learning process. More specifically, it seeks to investigate whether the application of CT ensures students’ active participation in the learning and teaching process, creates friendly relationships between group members, improves students’ social skills, limits individuality and engages students’ self-expression, and improves students’ academic performance compared to traditional teaching where they work individually. The research sample consisted of two hundred and ten Greek teachers. A structured questionnaire was used to conduct the research and collect data. The main findings of the research are summarized as follows: (i) A fairly high percentage of teachers state that the implementation of CT ensures the active participation of students in the learning and teaching process, creates friendly relationships between group members and improves students’ social skills; (ii) A high percentage of teachers state that the implementation of CT improves students’ academic performance compared to traditional teaching where they work individually.